(untitled) (KULT_online, 2016)
Since the independence of Nigeria in 1960, there has been intense discussion of the concept of art and of a genuinely Nigerian art within the context of the formation of a national identity superseding ethnic boundaries. In the book hereafter reviewed, titled „Jenseits von „Primitive Art“. Zum Selbstverständnis zeitgenössischer Künstler in Nigeria“, Stephanie Maiwald endeavours a description of the theoretical conceptualization of art and its fundamental dynamics in Nigeria since the 1960s. Based on interviews with local artists, she furthermore examines how contemporary African art is conceived by local Nigerian artists. It is not least the conditions under which artists work in the country that play a crucial role for a real comprehension of the local art scene and production.